2006
DOI: 10.1002/pssc.200669508
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of layered manganites BaLn 2 Mn 2 O 7 (Ln = rare earth)

Abstract: We have found that many phases appear in the layered manganites BaLn 2 Mn 2 O 7 , depending on the synthesis and annealing conditions for each rare earth metal. The BaLn 2 Mn 2 O 7 phase, with a stoichiometric composition synthesized under low oxygen pressure, transforms into another structure upon heating. The transition temperature varies according to the rare earth ion. In the present paper, we summarized the relationship between the transition temperature and rare earth ions. We successfully observed in-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Kamegashira has suggested that the tetragonal I 4/ mmm structure is stable at high temperatures 15 . The transition temperatures tend to increase with decreasing ionic radii of the Ln cations 14 . In the Gd–manganite, the tetragonal phase is reported to transform into another orthorhombic form at 773 K on heating 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Kamegashira has suggested that the tetragonal I 4/ mmm structure is stable at high temperatures 15 . The transition temperatures tend to increase with decreasing ionic radii of the Ln cations 14 . In the Gd–manganite, the tetragonal phase is reported to transform into another orthorhombic form at 773 K on heating 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, a new phase III started to nucleate in the low-temperature phase matrix at 277 • C, and the temperature agreed with the DSC and electrical conductivity results. 10,11 The complex pattern (e) can be interpreted as a mixture of the low-temperature phase (d) and the high-temperature phase (f). At around 500 • C, the intensity of 1 1 0 reflection became very weak, which indicated that the low-temperature phase nearly disappeared in (f).…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the first-order phase transformation may uniquely occur in layered perovskite with double-block oxygen octahedra. 10,14 The multiple transformations are related to the distortion of the structure. In the repeated trial, the transformation occurred slowly via the I4/mmm phase as a meta-stable phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in the cell dimensions indicate that the transition is irreversible by comparison of measurements on cooling and heating in XRD. 45) In general, phase transition is accompanied by tilting of the MnO 6 octahedra in the perovskite, and the symmetries change in the octahedral tilt system. In this case, however, the first-order phase transition occurred even in BaPr 2 Mn 2 O 7 (I4/mmm), which had no tilting of the octahedra.…”
Section: )mentioning
confidence: 99%